Usefulness of Global Coagulation Tests, Thrombin Generation and Viscoelastic Tests for Assessing the Bleeding Phenotype in Rare Coagulation Factor Deficiencies - Dreier, Tim; Mehic, Dino; Gebhart, Johanna (Hämostaseologie, 2025)
Inherited deficiencies of coagulation factors are rare and exhibit variable associations with severe bleeding phenotypes. Although conventional hemostatic assays serve as useful screening tools, they often fail to accurately predict clinical bleeding severity. Disease management is further complicated by poor correlation between residual factor levels and the overall symptom severity in affected patients and limited clinical experience. In this review, we evaluate the utility of global coagulation tests, such as the thrombin generation assay, plasmin generation assay (PGA), and rotational thromboelastometry (ROTEM), in assessing the severity of rare coagulation factor deficiencies and their clinical manifestations.Overall, thrombin generation, plasmin generation, and ROTEM were impaired in most rare coagulation factor deficiencies. Furthermore, significantly reduced coagulation factor activity and consequently decreased thrombin generation potential correlated with the clinical bleeding severity in deficiencies of prothrombin and factors V, VII, X, and XI. PGA was significantly impaired in fibrinogen and prothrombin deficiency and variably reduced in FV- and FX-deficient patients, but did not correlate with the presence or severity of bleeding manifestations. Lastly, ROTEM parameters were able to discriminate between asymptomatic FX-, FXI-, and fibrinogen-deficient patients and those with a history of bleeding.Although these studies are mostly limited to small sample sizes and prospective data are lacking, the available literature suggests that TGA, PGA, and ROTEM may be useful in stratifying patients according to their overall bleeding severity, as well as their risk of major bleeding complications in some of the rare coagulation factor deficiencies.
Keywords: inherited bleeding disorders; coagulation factor deficiency; thrombin generation assay; rotational thromboelastometry; routine hemostatic tests